The Effectiveness of Whole Brain Teaching and Reciprocal Teaching in Reading to Visual and Auditory Students - Lahita, Nanda; Mujiyanto, Januarius; Sutopo, Djoko (English Education Journal, 2018)
This study aimed analyzing the effectiveness of Whole Brain Teaching and Reciprocal Teaching to teach reading comprehension to visual and auditory students in MTs Qodiriyah. The subject of this research was eight graders. Class VIII A was as the experiment class 1 and class VIII C was as experiment class two. Every class consisted of 30 students (15 visuals and 15 auditory). This study was experimental research design by using 2x2 factorial designs. The data collection was done by giving visual auditory kinaesthetic (VAK) and reading comprehension tests. The data was analyzed by using t-test and ANOVA. The study revealed results that Whole Brain Teaching and Reciprocal Teaching were effective to teach reading comprehension to visual and auditory students. Reciprocal Teaching gave better effect than Whole Brain Teaching in teaching reading comprehension to both visual and auditory students. The last, there was no interaction between teaching techniques, studentsâ reading comprehension, and learning styles. In conclusion, both Whole Brain Teaching and Reciprocal Teaching were effective applied in teaching reading comprehension to visual and auditory students. Although there was no interaction between three variables, the fact showed studentsâ reading comprehension achievement was influenced by the teaching techniques not the studentsâ learning styles